AC-AC Voltage Controller of Power Supply for Heater on Drying System - Renny Rakhmawati; Farid Dwi Murdianto (Universitas Ahmad Dahlan, 2018)
The coconut fruits is very useful to be processed into cooking oil and it can meet the needs of cooking for Indonesia people, But before the coconuts processed into oil, The coconuts should be dried first. Usually the drying process is manually, that is dried in the sun. Unfortunately this way is not hygienic and can’t be done continuously, causing the coconut fungus overgrow. This paper proposes methode to solve the problem above.This research makes the dryer coconut fruitssystem by using the heater.Dryer system used for dry some coconut fruits that must be reduced the water content up to 5%, this dry coconutis called copra. System requires heater which will be regulated the temperature. Heater temperature setting is done by adjusting the heater supply voltage, and this is the task of ac to ac voltage controller. Ac to ac voltage controller is a circuit converter is capable converting ac voltage with value 220 Vrms at 50 Hz frequency and have waveform pure sinusoidal become ac voltage frequency at 50 Hz with an output voltage suitable with our need but the voltage waveform not impure sinusoidal or defective as a result firing angle effects. The output voltage which we set determines the value of the heater temperature. The output voltage is set from the firing angle of the triac component using the addition and decreasing angle values. Based on the results of experiments that have been done, if the drying chamber which has volume 135.2 liters and the temperature regulated at 700 C then the heater with a power requirement of 400 W should receive supply 216 V from ac to ac voltage controller. So the triac of ac to ac voltage controller fired on 0.55 radians so that the to ac voltage controller that gets 220 V input voltage can produce 216 V output voltage.